2004
DOI: 10.1021/ma0481712
|View full text |Cite
|
Sign up to set email alerts
|

A Morphological Study of a Semicrystalline Poly(l-lactic acid-b-ethylene oxide-b-l-lactic acid) Triblock Copolymer

Abstract: Poly(l-lactic acid-b-ethylene oxide-b-l-lactic acid) (PLLA-b-PEO-b-PLLA) triblock copolymers were synthesized by a ring-opening polymerization. PLLA and PEO sequentially crystallized by slowly cooling (−2 °C/min) from the melt. In the resultant spherulitic morphology, the retardation of polarized light was additive, and the sign of the spherulite (negative) was preserved when the PEO crystallized within the framework established by the PLLA crystals. Homopolymer blends of PLLA and PEO having the same compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
101
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(116 citation statements)
references
References 24 publications
(43 reference statements)
9
101
0
Order By: Relevance
“…When phase separation occurred, due to the dynamic competition between phase separation and crystallization process, PEG lamellas tended to array along different directions and formed different spherulitic morphology forms [32,44]. As Block7800 was proved to be crystalline-amorphous, the resulting crystal morphologies can be significantly influenced by microphase separation [5,6]. That may help to explain the formation of double concentric spherulites discovered in our study.…”
Section: Formation Of Double Concentricsupporting
confidence: 50%
See 2 more Smart Citations
“…When phase separation occurred, due to the dynamic competition between phase separation and crystallization process, PEG lamellas tended to array along different directions and formed different spherulitic morphology forms [32,44]. As Block7800 was proved to be crystalline-amorphous, the resulting crystal morphologies can be significantly influenced by microphase separation [5,6]. That may help to explain the formation of double concentric spherulites discovered in our study.…”
Section: Formation Of Double Concentricsupporting
confidence: 50%
“…Block copolymers, consisting of both crystalline and amorphous segments were widely recognized that their crystallization processes and the resulting crystal morphologies can be significantly influenced by microphase separation in melt [6,7]. However, block copolymers, consisting of different crystalline segments such as the double crystalline block copolymers, usually exhibit much more complicated crystallization behaviors [8,9], including confined crystallization [10][11][12][13], competitive or interactive crystallization and so on [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Similar diluent effects on the PLLA blocks have been observed in PLLA-b-PEO diblock copolymer with increasing the composition of poly(ethylene oxide) (PEO) block. 40,41 In a recent work we have demonstrated the effect of segregation strength on the development of crystallinity in symmetric diblock copolymers. 42 We have observed that with increasing value of segregation strength, the degree of crystallinity gradually decreases producing smaller and thinner crystals.…”
Section: Isothermal Crystallization Of Poly(p-dioxanone)-b-pcl (Ppdx-mentioning
confidence: 99%
“…Generally the spherulite sign is derived from the chain orientation along or across the spherulite circle. 10 In X-ray diffraction (XRD) diagrams of as-cast films (Figure 2a), some intense diffraction peaks assigned to PEG crystals 11 appeared in the 2 (: diffraction angle) range more than 10 while a very weak peak of PBLA blocks 12 appeared at 2 ¼ 5 , indicating that spherulites formed mainly as a result of PEG block crystallization. In addition, a sharp diffraction peak appeared at 2 ¼ 2 corresponding to a d-spacing of 4.4 nm, which demonstrates the formation of a long-range structure.…”
Section: Structure In Dry Statementioning
confidence: 99%